Social Media as an Electoral Machine: An Analysis of the Impact of Tragic Story Virality on Voter Behavior in the 2024 North Maluku Gubernatorial Election - Aji Deni (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
This research analyzes the role of social media as an election machine, focusing on the impact of tragic story virality on voter behavior in the 2024 North Maluku Gubernatorial Election (Pilgub). This study aims to identify how tragic narratives, such as the death of gubernatorial candidate Benny Laos, are utilized to frame public opinion and influence election outcomes. Using qualitative methods through social media content analysis (Twitter, Facebook and TikTok) and interviews with voters, this study shows that the virality of tragic stories triggers polarization and emotional mobilization of voters, especially the younger generation. The main results revealed that tragedy content was massively disseminated by buzzers and influencers, giving rise to political martyr narratives and conspiracy theories. This successfully capitalized on public emotions into tangible electoral support for Sherly Tjoanda, with a 22% increase in electability and the completion of the candidate transition in 7 days due to digital pressure. Despite the success of the emotional campaign, findings showed 62% of voters doubted Sherly's leadership capacity post-election. This research concludes that the virality of tragic stories can be a determinant of electoral victory, but has the potential to erode political rationality and create ethical dilemmas in the democratic process.